2023
DOI: 10.1097/tp.0000000000004542
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Proteomics in Transplantation: Identification of Injury and Rejection Markers

Abstract: Solid organ transplantation saves thousands of lives suffering from end-stage diseases. Although early transplants experienced acute organ injury, medical breakthroughs, such as tissue typing, and use of immunosuppressive agents have considerably improved graft survival. However, the overall incidence of allograft injury and chronic rejection remains high. Often the clinical manifestations of organ injury or rejection are nonspecific and late. Current requirement for successful organ transplantation is the ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…About the lifelong consequences of IS, Zubair et al 49 used RT-qPCR to analyze urine samples from patients under tacrolimus based immunosuppressant regimen and proposed a 7-gene signature by analyzing urine samples (7 genes) that was able to distinguish patients with nephrotoxicity related to calcineurin inhibitors with an ROC curve of 0.85. Wang et al 50 presented an interesting study using a combination of in vitro and airway organoid models to test the effect of different immunosuppressants on the replication of varying coronavirus variants.…”
Section: Immunosuppression Rejection and Tolerance After Liver Transp...mentioning
confidence: 99%
“…About the lifelong consequences of IS, Zubair et al 49 used RT-qPCR to analyze urine samples from patients under tacrolimus based immunosuppressant regimen and proposed a 7-gene signature by analyzing urine samples (7 genes) that was able to distinguish patients with nephrotoxicity related to calcineurin inhibitors with an ROC curve of 0.85. Wang et al 50 presented an interesting study using a combination of in vitro and airway organoid models to test the effect of different immunosuppressants on the replication of varying coronavirus variants.…”
Section: Immunosuppression Rejection and Tolerance After Liver Transp...mentioning
confidence: 99%
“…Enhancing the effector function of therapeutic cells with CRISPR/Cas9 based genome editing, providing one potential solution (20)(21)(22). However, current studies have identified limited genetic targets that can effectively regulate the immune cells in transplantation (23). Exploring new intervention targets for immunosuppressant and cellular immunomodulatory therapies is urgent.…”
Section: Current Application Of Highthroughput Crispr Technology In S...mentioning
confidence: 99%
“…The best treatment for kidney failure is organ transplantation. However, the incidence of organ rejection is high, and non-invasive biomarkers for early diagnosis of rejection are required [ 221 ]. Given the marker potential of IL-6 levels in the urine as a read-out for kidney function (see above Section 2.6.3 , Section 2.6.4 and Section 2.6.5 ), IL-6 concentrations were monitored over the first 30 postoperative days in 40 patients receiving renal transplants.…”
Section: Adipokines In Urine and Fecesmentioning
confidence: 99%